1999
DOI: 10.1146/annurev.cellbio.15.1.607
|View full text |Cite
|
Sign up to set email alerts
|

Transport Between the Cell Nucleus and the Cytoplasm

Abstract: The compartmentation of eukaryotic cells requires all nuclear proteins to be imported from the cytoplasm, whereas, for example, transfer RNAs, messenger RNAs, and ribosomes are made in the nucleus and need to be exported to the cytoplasm. Nuclear import and export proceed through nuclear pore complexes and can occur along a great number of distinct pathways, many of which are mediated by importin beta-related nuclear transport receptors. These receptors shuttle between nucleus and cytoplasm, and they bind tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
1,703
1
14

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,880 publications
(1,758 citation statements)
references
References 339 publications
23
1,703
1
14
Order By: Relevance
“…The classical concept applies for nuclear import of proteasomes. Thus, we will focus on the key components required for the classical pathway ( Gorlich & Kutay, 1999). …”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The classical concept applies for nuclear import of proteasomes. Thus, we will focus on the key components required for the classical pathway ( Gorlich & Kutay, 1999). …”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…Ran is a small GTPase, named Gsp1 in yeast. Ran exists in its GTP-bound state in the nucleus and in its GDP-bound state in the cytoplasm due to the actions of the Ran guanine nucleotide exchange factor (RanGEF) and the RanGTPase activating protein (RanGAP) in the nucleo- and cytoplasm, respectively ( Gorlich & Kutay, 1999; Moore & Blobel, 1993). In the nucleus, the cargo-importin αβ complex encounters RanGTP, which results in the release of the cargo ( Rexach & Blobel, 1995).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…The ~50 kDa AID-GFP is at the upper limit of the nuclear pore cut-off 29,30 . We confirmed that AID could mediate active nuclear import by increasing the size of the fusion protein so as to preclude diffusion.…”
Section: Aid Is Actively Imported Into the Nucleusmentioning
confidence: 99%
“…We confirmed that AID could mediate active nuclear import by increasing the size of the fusion protein so as to preclude diffusion. Since protein shape may strongly influence the ability to diffuse 30 , we used APOBEC2 (A2) as control. Given the homology with A2 and APOBEC3G [31][32][33] , the predicted three-dimensional structure of AID safely allows us to postulate that the monomers of A2 (25.7 kDa) and AID (23.9 kDa) will have a similar general folding, and therefore shape ( Supplementary Fig.…”
Section: Aid Is Actively Imported Into the Nucleusmentioning
confidence: 99%
“…The existence of the nucleus in eukaryotic cells necessitates efficient mechanisms to exchange macromolecules between the nucleus and the cytoplasm+ Many proteins and RNAs are transported across the nuclear envelope through the nuclear pore complexes (NPCs)+ Identification of importin-b family members as major nucleocytoplasmic transport receptors has greatly enhanced our understanding of nuclear transport mechanisms, and has enabled the development of simple but robust models of import and export processes (reviewed in Cole & Hammel, 1998;Dahlberg & Lund, 1998;Izaurralde & Adam, 1998;Mattaj & Englmeier, 1998;Ohno et al+, 1998;Görlich & Kutay, 1999;Hood & Silver, 1999)+ In these models, an import receptor binds to a cargo and carries it into the nucleus+ The receptor then binds to RanGTP (the nuclear form of Ran), resulting in release of the cargo+ In the case of export, an export receptor binds to a cargo in the nucleus cooperatively with RanGTP, forming a trimeric export complex+ This complex moves to the cytoplasm and disassembles due to GTP hydrolysis triggered by Ran's GTPase activating factors in the cytoplasm+ Export of RNA cargoes usually requires more complex mechanisms+ One example of this is U snRNA export+ Major spliceosomal U snRNAs such as U1, U2, and U5 are transcribed in the nucleus by RNA polymerase II and acquire a monomethylated cap structure+ In metazoa, these U snRNAs are initially exported from the nucleus+ They bind in the cytoplasm to a group of proteins termed the Sm proteins+ Subsequently the cap structure is hypermethylated, and the RNA-protein complexes (snRNPs) are imported back to the nucleus, where they take part in pre-mRNA splicing reactions (Mattaj, 1988;Lührmann et al+, 1990)+ It has been shown that the monomethyl cap structure is the only essential signal for U snRNA export and that the leucine-rich nuclear export signal (NES) receptor CRM1/ Exportin 1 (Xpo1) mediates this RNA export (Hamm & Mattaj, 1990;Jarmolowski et al+, 1994;Fischer et al+, 1995;Fornerod et al+, 1997)+…”
Section: Introductionmentioning
confidence: 99%